Teacher Education Policy Issues in Poland: Recommendations for Building a High-Quality Teaching Profession - Madalińska-Michalak, Joanna (Kultura-Społeczeństwo-Edukacja, 2020)
While there is general agreement that we need to increase the quality of education, there is less agreement on the measures to be taken. This paper focuses on the need to build the high-quality teaching profession to respond to the changing role of teachers in the twenty first century. It is argued that changes in the system of education should include a central place for the teacher and the quality of teacher education. The paper looks at selected aspects of teacher education policy in relation to the Bologna process and changes that were implemented at different levels of the system of education in Poland. A specific concern of this paper is policies that contribute to raising teacher education quality in a way which responds to the challenges of teachers preparation, recruitment, work and careers, and especially teachers’ lifelong learning. The implications of the analysis are that teacher education policy development in Poland should focus on futher actions for attracting to the teaching profession the best candidates and for retaining the best teachers in the school system in order to build a high-quality teaching profession. Some measures for achieving these goals are proposed.